Delivery of Oligonucleotides Using a Self-Degradable Lipid-Like Material - Hiroki Tanaka; Nae Takata; Yu Sakurai; Tokuyuki Yoshida; Takao Inoue; Shinya Tamagawa; Yuta Nakai; Kota Tange; Hiroki Yoshioka; Masatoshi Maeki; Manabu Tokeshi; Hidetaka Akita (MDPI AG, 2021)
The world-first success of lipid nanoparticle (LNP)-based siRNA therapeutics (ONPATTRO®) promises to accelerate developments in siRNA therapeutics/gene therapy using LNP-type drug delivery systems (DDS). In this study, we explore the optimal composition of an LNP containing a self-degradable material (ssPalmO-Phe) for the delivery of oligonucleotides. siRNA or antisense oligonucleotides (ASO) were encapsulated in LNP with different lipid compositions. The hepatic knockdown efficiency of the target genes and liver toxicity were evaluated. The optimal compositions for the siRNA were different from those for ASO, and different from those for mRNA that were reported in a previous study. Extracellular stability, endosomal escape and cellular uptake appear to be the key processes for the successful delivery of mRNA, siRNA and ASO, respectively. Moreover, the compositions of the LNPs likely contribute to their toxicity. The lipid composition of the LNP needs to be optimized depending on the type of nucleic acids under consideration if the applications of LNPs are to be further expanded.